Worry about crime and loneliness in nine countries of the former Soviet Union. (March 2023) - Stickley, Andrew; Kondo, Naoki; Inoue, Yosuke; Kanamori, Mariko; Kino, Shiho; Arakawa, Yuki; McKee, Martin
Abstract: Worry about crime has been linked to several detrimental outcomes including worse mental health. However, there has been little research on the association between worry about crime and loneliness, even though loneliness is increasingly being recognised as a serious public health issue. To address this deficit, this study examined the association between worry about crime and loneliness in nine countries of the former Soviet Union (FSU - Armenia, Azerbaijan, Belarus, Georgia, Kazakhstan, Kyrgyzstan, Moldova, Russia, and Ukraine), using data from 18, 000 respondents aged 18 and above that were collected during the Health in Times of Transition (HITT) survey in 2010/11. Results from a pooled logistic regression analysis showed that compared to those who reported no worry about crime, individuals with a high level of worry had significantly higher odds of loneliness (odds ratio [OR]: 1.43, 95% confidence interval [CI]: 1.17–1.75). Sex- and age-stratified analyses further showed that the association was observed in women with a mid (OR: 1.37, 95%CI: 1.10–1.71) and a high level (OR: 1.70, 95%CI: 1.33–2.17) of worry about crime but not in men, and that a high level of worry about crime was linked to loneliness in adults aged 35–59 (OR: 1.39, 95%CI: 1.02–1.91) and 60 and above (OR: 1.64, 95%CI: 1.12–2.40) but not in those aged 18–34. High levels of worry about crime are associated with loneliness in the FSU countries. Reducing crime and its associated worries may have important public health benefits in these countries. Highlights: A high level of worry about crime was associated with higher odds for loneliness. Worry about crime was linked to loneliness in women but not men. Worry about crime was associated with loneliness in middle-aged and older adults. Reducing crime-related worries may have important public health benefits.